PERUBAHAN KAMPUNG KOTA (Pengaruh Hadirnya Mall Dan Hotel Terhadap Pemukiman Masyarakat Kampung Sekayu Dan Jayenggaten Dalam Perubahan Sosial Di Semarang Abad Ke 21) - Muhamad Soni Gunawan; Akhmad Ramdhon (Universitas Sebelas Maret (UNS), 2019)
This study is qualitative research using a phenomenological approach in which the researcher tries to understand the meaning of the events of change in Kampung Sekayu and Jeyenggaten and their links to the social conditions of society. Data collection in this research uses document examination, in-depth interviews, Focused Group Discussion (FGD), directed discussion, and observation. The data obtained were then analyzed using the Interactive Model Analysis technique.Kampung Sekayu and Jeyenggaten began to disappear along with the presence of malls and hotels in the region. Conflict experienced by Sekayu with Mall Paragon in city development solely leaves the Sekayu urban village office only. Changes occurred in RT 1 with a total of around 33 houses being dismissed. The surrounding area turned into a land for selling residents, which also affected the road constriction. Citizens' houses also have diverse functions, no longer a place to live but become rental or boarding houses and laundry businesses. Moreover, Kampung Jayenggaten's existence has engulfed by the magnificent Gumaya Tower in 2005. From 30 buildings leaving only 1 building left. Glance no more usual lives of Jayenggaten residents. The impact to this day has been held by residents of the next village who suffers from increasingly limmited water supply due to the construction of the hotel.Local regulations determine that the area is no longer allowed as a residential area, but as an office and business area also took part in the loss of the Kampung Sekayu and Jeyenggaten. Semarang City Landscape Planning which prioritized economic interests also forced the indigenous resident to leave and move to the outskirts area and form a new identity.